(untitled) (Swiss Medical Weekly, 2015)
OBJECTIVES: We aimed to explore acute kidney injury (AKI) Kidney Disease Improving Global Guidelines (KDIGO) stage 2 to 3 in a cohort of antiretroviral treated HIV-infected individuals. METHODS: HIV-infected individuals of the Swiss HIV Cohort Study (Basel site), treated with combination antiretroviral therapy (cART) 2002–2013, were included. AKI was defined and classified according to the KDIGO Clinical Practice Guidelines for AKI. Data were prospectively collected and reports of kidney biopsies obtained from records. RESULTS: Among 1,153 cART-treated patients, 13 experienced AKI KDIGO stage 2 to 3 (1 patient stage 2, 12 patients stage 3; median age 46 years; 9 male; median CD4 count 366 cells/μl), corresponding to an incidence rate of AKI of 0.77 (95% confidence interval 0.45–1.33) per 1000 patient-years. Baseline estimated glomerular filtration rate (eGFR) was 87 ml/min (interquartile range 66–100). Ten patients were treated with tenofovir (TDF). Nine patients (69%) had ≥1 cardiovascular risk factor, only two patients had known pre-existing kidney disease. Three patients needed chronic and two temporary dialysis. AKI was associated with TDF therapy in 6 of 13 (46%) patients (mean TDF exposure time before AKI 41 months). Impaired renal function was partially reversible in all patients. In three patients with biopsy-proven pre-existing kidney disease (AA amyloidosis, calcineurin inhibitor-induced nephropathy and minimal change glomerulopathy), TDF potentially added to AKI. CONCLUSIONS: AKI KDIGO stage 2 to 3 demonstrates complex associations at the individual level and can occur without early signs. Although treatment with TDF and presence of cardiovascular risk factors were found frequently, predicting AKI seems very difficult.